Risk of hepatocellular carcinoma in Asian patients with primary biliary cholangitis: A nationwide and hospital cohort study - Jihye Lim; Ye-Jee Kim; Sehee Kim; Jonggi Choi (JHEP Reports)
Background & Aims: Large-scale studies on the association between primary biliary cholangitis (PBC) and hepatocellular carcinoma (HCC) in Asians are scarce. This study aimed to evaluate the incidence of HCC and its risk factors in a nationwide cohort. Methods: The data of 4,882 patients with PBC and 38,603 matched controls were extracted from the Korean National Health Insurance Service (2007–2020) and analyzed. The incidence of HCC and its risk factors in patients with PBC were assessed and compared with those in the matched controls. The results were validated in a multicenter hospital cohort of 862 patients with PBC, recruited from Asan Medical Center (n = 815) and Yeouido St. Mary’s Hospital (n = 47) in Korea. Results: In total, 105 patients with PBC developed HCC over the median follow-up period of 5.42 years, yielding an incidence rate of 3.7/1,000 person-years (PYs), which was significantly higher than that in the controls (0.5/1,000 PYs; adjusted hazard ratio: 9.07; 95% CI: 6.71–12.27). PBC, older age, male sex, diabetes, and smoking were identified as significant risk factors for HCC. Twenty-three of the 862 patients with PBC developed HCC in the multicenter hospital cohort, yielding an incidence of 4.0/1,000 PYs (95% CI: 2.4–5.7). Older age (subdistribution hazard ratio [SHR]: 1.05, 95% CI: 1.00–1.10), male sex (SHR: 3.00, 95% CI: 1.11–8.13), current alcohol consumption (SHR: 3.70, 95% CI: 1.08–12.59), and cirrhosis (SHR: 5.17, 95% CI: 2.07–12.93) were identified as risk factors in the hospital cohort. Conclusions: Patients with PBC were at a significantly higher risk of developing HCC. Older age and male sex were consistent risk factors in both cohorts. Impact and implications:: Notable heterogeneity has been observed among different studies in terms of the incidence of hepatocellular carcinoma (HCC) in patients with primary biliary cholangitis (PBC). Large-scale studies on the association between PBC and HCC in Asians are scarce. In our nationwide cohort study, patients with PBC exhibited a significantly heightened risk of developing HCC and mortality than the age- and sex-matched controls. Individuals with PBC had a 9.1-fold higher risk of developing HCC than their matched counterparts, with an incidence rate of 3.7/1,000 person-years. Older age, male sex, smoking, and diabetes were identified as prominent risk factors for HCC in patients with PBC in the nationwide cohort. Older age, male sex, and alcohol consumption were identified as the factors significantly contributing to the elevated risk of HCC in patients with PBC in validation multicenter hospital cohort.